Literature Study on the Role of E-Budgeting in Increasing APBD Transparency - Fachrulla, Arfa; Arifuddin Mas'ud; Mulyati Akib (PT. Banjarese Pacific Indonesia, 2025)
This study aims to analyze the relationship between individual behavior in the implementation of e-government and the implementation of e-budgeting to support the principle of transparency of the Regional Revenue and Expenditure Budget (APBD) and achieve good governance. E-government as a digital transformation in the government sector aims to improve efficiency, transparency, and accountability in the management of public administration. However, its success is highly dependent on individual behavior, including acceptance and adaptation to technology. E-budgeting, as one form of e-government implementation, is designed to increase transparency by providing easy and real-time access to the public regarding information on the use of the APBD. This study uses a literature study approach by reviewing various scientific articles and related documents from 2020 to 2024. The results of the study show that individual behavior, such as digital literacy and attitudes towards technology, play an important role in determining the success of e-government and e-budgeting. Although e-budgeting is able to increase transparency, challenges such as resistance to change, limited infrastructure, and low public trust in the government remain significant obstacles. Therefore, strategic steps such as community empowerment through digital literacy, increasing human resource capacity, and more effective communication between the government and the community are needed to ensure the success of this system. This research is expected to be a theoretical basis in developing a more effective e-government and e-budgeting implementation strategy in the future.